当3a^2+ab-2b^2=0(a和b都不等于0),求a/b-b/a-(a^2+b^2)/ab的值

4个回答

  • a/b-b/a-(a^2+b^2)/ab将其通分得(a^2-b^2-a^2-b^2)/ab再化简得-2b/a

    因为(a+b)^2=a^2+2ab+b^2

    所以ab=【(a+b)^2-a^2-b^2】/2

    代入3a^2+ab-2b^2=0得:3a^2+【(a+b)^2-a^2-b^2】/2-2b^2=0

    所以【6a^2+(a+b)^2-a^2-b^2-4b^2】/2=0

    所以6a^2+(a+b)^2-a^2-b^2-4b^2=0

    所以5a^2-5b^2+(a+b)^2=0

    所以5(a^2-b^2)+(a+b)^2=0

    所以5(a+b)(a-b)+(a+b)^2=0

    分情况:1.当a+b不等于0时,该式同时除a+b得5(a-b)+(a+b)=0

    去括号:6a-4b=0

    所以b=3a/2

    所以b/a=3/2

    所以-2b/a=-3

    2.当a+b=0时,有a=-b

    所以-2b/a=2

    综上所述:a/b-b/a-(a^2+b^2)/ab的值为-3或2